The Role of the Tring by Pegadaian Application as a Digital Innovation at UPS Madina - Alimuddin Alimuddin; Derliani Derliani; Dian Hidayat; Dia Lestari; Yenni Abdina Sari; Nur Amalia; Nurhadijah Nurhadijah; Samsir Alam (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2026)
This study aims to analyze the role of the Tring by Pegadaian application as a digital innovation in improving service effectiveness at the Madina Sharia Service Unit (UPS). The study used a qualitative approach with a descriptive research type. Data were obtained through observation, in-depth interviews, and documentation involving unit leaders, employees, and customers. The results show that the implementation of the Tring application at UPS Madina is part of the digital transformation undertaken by PT Pegadaian to improve service quality. The Tring application plays a role in increasing service time efficiency, ease of transaction access, and information transparency for customers. The use of this application also contributes to reducing queues and increasing the accuracy of transaction recording through an integrated system. However, the application's utilization is not fully optimal due to obstacles in customer digital literacy, limited internet network, and people's habits that still prefer conventional services. Therefore, increased socialization, digital education, and infrastructure support are needed to maximize the implementation of this digital innovation. This research is expected to serve as a reference for developing service digitalization strategies at Islamic financial institutions at the regional level.